Microsoft Scrolling Strip Prototype: Technical Description - Hinckley, Ken (2000)
Several exemplar embodiments of a touch-sensitive strip are shown in Figure 1. In general, the scrolling strip has a main scrolling area, an up scrolling region, and a down scrolling region. In some embodiments, the up and down scrolling areas are physically separate from the main scrolling area.